“Nangañaña” (Tremelloscypha gelatinosa, Sebacinaceae), a wild edible fungus from the tropical deciduous forest of the Central Chiapas Basin, Mexico - Bandala, Victor Manuel; Montoya, Leticia; Villegas, Rafael; Cabrera, Teresa Guadalupe (Instituto de Ecología, A.C., 2014)
We present information on the use of sporomes of Tremelloscypha gelatinosa as a food source among native people from Nandayalu, a locality situated SE of Tuxtla Gutiérrez, Chiapas, Mexico. The fungus is locally named “nangañaña” and its fruit bodies are collected during part of the rainy season (June-August) and are used for familiar consumption. Their methods of collecting and preparation are described and photographs of the basidiomes and habit are provided. Tremelloscypha gelatinosa was found growing below trees of Gymnopodium floribundum in the tropical deciduous forest of the Central Chiapas basin. It is a heterobasidiomycete belonging to the order Sebacinales and its phylogenetic placement among proven ectomycorrhizal sebacinoid species suggests its probable ectomycorrhizal symbiosis with plant roots, thus playing a relevant ecological role in tropical ecosytems where it occurs. Tremelloscypha gelatinosa is an infrequently encountered fungus, currently known from Jamaica (type locality), Florida (USA), Yucatán and Quintana Roo (Mexico) and until now unreported as a wild edible fungus.